KONSTRUKSI PEMBERITAAN KASUS BODY SHAMING ARTIS DIAN NITAMI DI NAKITA.GRID.ID DAN TEMPO.CO - Anggun Putri Dewanggi; Laksmi Rachmaria (Communication, 2019)
Body shaming is an act of mocking or insulting by commenting on a person's physical form or body size. Body shaming is synonymous with bullying behavior, because it will affect one's self-image, self-concept, and self-confidence. This study aims to see how the construction of body shaming reports that hit Dian Nitami artists in Tempo.Co and Nakita.Id online media. The research approach used in this study is qualitative with a constructivist paradigm. This study uses Robert N. Entman's Framing Theory. Research results: Tempo.Co in its frame brings the case of bullying that befell Dian Nitami artists to the realm of law. Tempo.Co positions the account @corissa.putrie owner as the cause of the problem and Anjasmara as a hero. Make Moral Judgment which is presented by Tempo.Co in the news in the form of a threat of punishment that will be accepted by the body shaming perpetrators on social media. Treatment Recommendation offered by Tempo.Co in its news text so that people are wiser and wiser in speaking on social media. Nakita.Id brought this case to the moral realm. Nakita.Id positioned the @corissa.putrie account and also the women who use social media as the cause of the problem, Anjasmara is positioned as Dian Nitami's hero and artist as a victim. The Make Moral Judgment presented by Nakita.Id was an appeal to reflect on what we had typed with the fingers and uploaded to the internet. Treatment Recommendations are offered so that every citizen takes heed of ethics in social media. Conclusion: media is a means for people to understand various realities. through the construction of news reporters display and place events in a particular social context where the audience is.